THE MAHATMA OF COMMUNICATION - Vaishnav, Harmik (PEOPLE: International Journal of Social Sciences, 2019)
Communication of any type has its root in the person’s personality and psyche. Person’s practices, philosophy and beliefs and clarity of means and ends affect his/ her communication style, use of words etc. Communication for Gandhi was the output of lot of thought process combined with experience and experiment and his words would come out with utmost clarity and conviction in an understandable language. If we want to see Gandhi from two sides they are as simple as the man himself: action and communication and communication and action. He was an enormous communicator and his communication ranged from individual to mass communication, from speeches to discussions, from writing to body language and from symbols to silence. This communication made him reach out to the rich and the poor, to the metros and hamlets, to the illiterate and the celebrities and intellectuals. The enormity of the reach of his communication and the penetration cannot be fathomed easily. In this article there is humble try to analyse Gandhi’s communication style and manner, the impact of his communication and what lessons can be gained from his method of communication.